A composite neurobehavioral test to evaluate acute functional deficits after cerebellar haemorrhage in rats. Issue 3 (March 2018) - McBride, Devin W; Nowrangi, Derek; Kaur, Harpreet; Wu, Guangyong; Huang, Lei; Lekic, Tim; Tang, Jiping; Zhang, John H
Cerebellar haemorrhage accounts for 5–10% of all intracerebral haemorrhages and leads to severe, long-lasting functional deficits. Currently, there is limited research on this stroke subtype, which may be due to the lack of a suitable composite neuroscoring system specific for cerebellar injury in rodents. The purpose of this study is to develop a comprehensive composite neuroscore test for cerebellar injury using a rat model of cerebellar haemorrhage. Sixty male Sprague-Dawley rats were subjected to either sham surgery or cerebellar haemorrhage. Twenty-four hours post-injury, neurological behaviour was evaluated using 17 cost-effective and easy-to-perform tests, and a composite neuroscore was developed. The composite neuroscore was then used to assess functional recovery over seven days after cerebellar haemorrhage. Differences in the composite neuroscore deficits for the mild and moderate cerebellar haemorrhage models were observed for up to five days post-ictus. Until now, a composite neuroscore for cerebellar injury was not available for rodent studies. Herein, using mild and moderate cerebellar haemorrhage rat models a composite neuroscore for cerebellar injury was developed and used to assess functional deficits after cerebellar haemorrhage. This composite neuroscore may also be useful for other cerebellar injury models.